Global weak solutions to the compressible Cucker–Smale–Navier–Stokes system in a bounded domain. (July 2023) - Chen, Li; Li, Yue; Zamponi, Nicola
Abstract: A coupled kinetic-fluid model is investigated, which describes the dynamic behavior of an ensemble of Cucker–Smale flocking particles interacting with a viscous fluid in a three-dimensional bounded domain. This system consists of a kinetic Cucker–Smale equation and a compressible Navier–Stokes system with nonhomogeneous boundary conditions. The global existence of weak solutions to this system with adiabatic coefficient γ > 3 / 2 is established.